Musculoskeletal structure and function in response to the combined effect of an obesogenic diet and age in male C57BL/6J mice. Issue 10 (30th June 2017) - Bott, Kirsten N.; Gittings, William; Fajardo, Val Andrew; Baranowski, Bradley J.; Vandenboom, Rene; LeBlanc, Paul J.; Ward, Wendy E.; Peters, Sandra J.
Abstract : Scope: The effects of a long‐term high fat and sucrose diet (HFS) superimposed with aging on bone and muscle structure and/or function. Methods and results: Male C57BL/6J mice (20 weeks of age) were randomized to 1 of 3 groups: baseline (BSL, n = 12), or assigned to a control (AGE, n = 12) or HFS (HFS‐AGE, n = 11) diet for 13 weeks. Trabecular bone structure, volumetric bone mineral density (vBMD), and body composition, were measured longitudinally at 20, 24, and 32 weeks of age. In vitro contractile measures were performed on isolated soleus and extensor digitorum longus (EDL) muscles for each group. Both AGE and HFS‐AGE had similar declines in trabecular bone structure, while HFS‐AGE resulted in increased soleus cross‐sectional area (CSA) compared to AGE, but this did not translate to greater twitch or tetanic peak force. The ratio of outcomes of bone to muscle declined in both AGE and HFS‐AGE compared to BSL as a result of greater declines in trabecular bone structure than muscle function. Conclusion: Consumption of a 13‐week HFS diet at 20 weeks of age did not exacerbate age‐related declines in bone or muscle, but these tissues do not decline in a coordinate manner with greater declines in bone than muscle. Abstract : With aging, the ratio of outcomes of bone and muscle structure and function decline in a noncoordinate manner regardless of an obesogenic diet intervention. Outcomes of bone structure decline while muscle outcomes are largely unchanged.